A Case of ACTH Independent Macronodular Adrenocortical Hyperplasia Presenting with Conns Syndrome - Menon, Neethika; Padmanabhan, Anitha; Gadgil, Nitin M; Patil, Milind V (Annals of Pathology and Laboratory Medicine, 2023)
Backgound: ACTH Independent macronodular adrenocortical hyperplasia (AIMAH)is a rare cause of hyperaldosteronism and is characterised by bilateral adrenal hyperplasia . One of the most common presenting symptoms is refractory hypertension. Clinical features and hypertension usually resolve following adrenalectomy. Timely diagnosis of such conditions are pertinent as they are completely treatable and thus prevents further comorbidities associated with hypertension and hypokalemia like arrhythmia. Case Presentation: A 57 year old male patient presented with unresolved hypertension since 15 years even after treatment with three different antihypertensives drugs since last one year. He was detected with raised serum aldosterone levels. Adrenal venous sampling showed lateralisation to the left adrenal. CT abdomen and pelvis revealed enlarged and nodular left adrenal gland and a bulky right adrenal gland. Laparoscopic left adrenalectomy was performed. Grossly left adrenal showed multiple well circumscribed yellow coloured nodules restricted to the cortex. Microscopy showed multiple well circumscribed unencapsulated nodules comprising of compact cells with clear to vacuolated cytoplasm and round central nucleus along with few foci of myelometaplasia. Conclusion: Conns syndrome causes a high rate of mortality and morbidity of left untreated. Serum aldosterone, serum cortisol and serum electrolyte levels should be carried out in every case of refractory hypertension to rule out adrenocortical lesions. Timely diagnosis goes a long way in reducing morbidities associated with hypertension and dyselectrolytemia.